The identification of plant reliefs in the Lalitavistara story of Borobudur temple, Central Java, Indonesia - Destario Metusala; Fauziah; Dewi Ayu Lestari; JANIS DAMAIYANI; SHOFIYATUL MAS’UDAH; HARI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Metusala D, Fauziah, Lestari DA, Damaiyani J, Mas’udah S, Setyawan H. 2020. The identification of plant reliefs in the Lalitavistara story of Borobudur temple, Central Java, Indonesia. Biodiversitas 21: 2206-2215. The Lalitavistara sutra is one of the central texts in the Mahayana tradition and it describes the life of the Buddha. This sutra has been carved in a good detail into 120 relief panels. These reliefs showed many plant figures that have often been carved in proper shape, so that made it possible for identification. The identification results showed that there were at least 63 species of plants in the Lalitavistara relief at Borobudur and these more various than species mentioned in the Lalitavistara sutra. Some species even only be found on reliefs but not in the text. These findings have indicated several important points; (i). the ancient Javanese community at that time already had a high awareness of the plant diversity, (ii). the plant figures as component in building atmosphere/background have been used by the carver as an opportunity for improvisation, (iii). the plant reliefs in Borobudur can be seen to reflect the surrounding plant diversity at the time, and (iv). the identification of plant reliefs in Borobudur can be used as an approach to understand the perspective of an ancient Javanese community on the importance of plant diversity.